THE FACTORS, CONSEQUENCES AND SOLUTIONS OF SPEAKING ANXIETY IN FOREIGN LANGUAGE CLASSROOMS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
It is extensively understood that four skills which are listening, reading, writing, speaking are involved in English learning. All of these skills are related to each other. Among four skills, speaking appears the most vital on a daily life. This belief is backed by Parmawati (2018 p.21) speaking is the most essential skill of English language since speaking mediates as communication tool of every -day life.